The extent to which the science book included the sixth grade of the developed primary concepts of health education - Albayati, Adnan Hekmat; Aljumali, Saja Sabah (Al-Adab Journal, 2020)
The research aims to identify the concepts of health education that should be included in the science book for the sixth grade of the developed primary. The researcher used the analytical descriptive method which is based on the content analysis using the content analysis form prepared by the researcher. Of the arbitrators, and then ensure their stability by re-analysis, and the card was formed in the final version of (5) main areas, of which (29) concept. The science book was chosen for the sixth grade developed for the academic year 2017/2018 and the number of pages analyzed (178) pages of the total pages of the book consists of (252) The researcher excluded questions and pictures from the analysis. Study Tool: Analysis of science book content for the sixth grade primary developer.